A Multi-Objective Optimization Model for Designing Business Portfolio in the Oil Industry - Kiamehr, A. K.; Azar, A.; Nayeri, M. D. (Engineering, Technology & Applied Science Research, 2018)
Designing a business portfolio is one of the key decisions in developing corporate strategy. Most of the previous models are either non-quantitative or financial with an emphasis on optimizing a portfolio of investments or projects. This research represents a multi-objective optimization model that firstly, employs quantitative methods in strategic decision-making, and secondly, quantifies and considers non-financial, strategic variables in problem modeling. In this regard, links between businesses within a portfolio have been classified into four groups of market synergy, capabilities synergy, parenting costs, and sharing benefits, and have been structured as a conceptual model. Although the conceptual model can be applied to various industries, it is formulated for designing the portfolio of multi-business companies in Iran oil industry. The model has been solved for three cases by NSGA-II algorithm and strategic insights have been explored for different corporate types.